Primary care physician beliefs and practices regarding blood pressure measurement: results from BP-CHECK qualitative interviews - Clarissa Hsu; Laurel Hansell; Kelly Ehrlich; Sean Munson; Melissa Anderson; Karen L. Margolis; Jennifer B. McClure; Yoshio N. Hall; Matthew Thompson; Dwayne Joseph; Beverly B. Green (BMC Primary Care, 2023)
Abstract Background Early identification and control of hypertension is critical to reducing cardiovascular disease events and death. U.S. Preventive Services Task Force guidelines recommend health care professionals screen all adults for hypertension, yet 1 in 4 adults with hypertension are unaware of their condition. This gap between guidelines and clinical practices highlights an important opportunity to improve blood pressure (BP) screening and hypertension diagnosis, including measurement outside of clinic settings. To identify targets for future diagnostic interventions, we sought to understand primary care physicians' (PCPs) beliefs and practices regarding use of common forms of BP measurement. Methods Study participants were PCPs (N = 27) who had patients enrolled in the BP-CHECK trial. The trial compared the accuracy of 24-h ambulatory BP monitoring (ABPM) to: 1) clinic-based monitoring, 2) home BP monitoring (HBPM), or 3) use of a BP kiosk in clinics or pharmacies. Physicians were interviewed by phone and compensated for their participation. Interviews were recorded, transcribed, and analyzed using a template analysis approach. Results Overall, PCPs preferred and trusted clinic BP measurement for diagnosing hypertension, particularly when measured with a manual sphygmomanometer. Concerns with HBPM included the belief that patients did not follow protocols for rest and body positioning at home, that home machines were not accurate, that home BPs could not be entered into the medical record, and that HBPM would make some patients anxious. Issues regarding kiosk measurement included beliefs that the public setting created stress for patients, that patients did not follow resting protocols when using kiosks, and concerns about the maintenance of these machines. ABPM was recognized as highly accurate but was not perceived as accessible. Additionally, some PCPs found it challenging to interpret the multiple readings generated by ABPM and HBPM, especially when these readings differed from clinic BPs. Conclusions Our findings suggest that both additional physician education and training and investments in equipment and system-level processes are needed to increase the acceptance and utilization of out of office BP measurement for identification and treatment of hypertension. These changes are needed to improve ensure everyone in the U.S receive optimal care for hypertension. Trial registration ClinicalTrials.gov NCT03130257 . Initial registration date: 4/21/2017.